2009
DOI: 10.1002/cbf.1603
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of cell death by 5‐aminolevulinic acid‐based photodynamic action and its enhancement by ferrochelatase inhibitors in human histiocytic lymphoma cell line U937

Abstract: Photodynamic therapy (PDT) for tumors is based on the tumor-selective accumulation of a photosensitizer, protoporphyrin IX (PpIX), followed by irradiation with visible light. However, the molecular mechanism of cell death caused by PDT has not been fully elucidated. The 5-aminolevulinic acid (ALA)-based photodynamic action (PDA) was dependent on the accumulation of PpIX, the level of which decreased rapidly by eliminating ALA from the incubation medium in human histiocytic lymphoma U937 cells. PDA induced apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 59 publications
2
39
1
Order By: Relevance
“…Research show that PDT might act on hyperproliferating cells, which selectively uptake ALA and undergo apoptosis and necrosis following PDT. 29 It also has been suggested that PDT may have immunomodulatory e®ect based on the fact that there is an increase in the CD8þ reaction in the damaged tissue following PDT. The initial pain and soreness indicate that there may be an in°ux of new T cells, followed by an overall reduction in the number of in°ammatory cells and tissue healing.…”
Section: Discussionmentioning
confidence: 99%
“…Research show that PDT might act on hyperproliferating cells, which selectively uptake ALA and undergo apoptosis and necrosis following PDT. 29 It also has been suggested that PDT may have immunomodulatory e®ect based on the fact that there is an increase in the CD8þ reaction in the damaged tissue following PDT. The initial pain and soreness indicate that there may be an in°ux of new T cells, followed by an overall reduction in the number of in°ammatory cells and tissue healing.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in erythrocyte zinc PPIX is an early indicator of iron deficiency and precedes the development of anemia (Labbe et al, 1999). Iron chelators can bind to ferrous iron in the cytoplasm of cells, such as hepatocytes, and prevent iron from entering mitochondria to reduce FECH function and cause PPIX accumulation (Amo et al, 2009;Blake and Curnow, 2010;Juzeniene et al, 2013). In rodent and chick embryo livers and isolated hepatocytes, iron chelation can limit heme synthesis sufficiently to potentiate induction of ALAS1 by drugs and steroids (Anderson et al, 1982).…”
Section: Disregulation Of Ppix Homeostasismentioning
confidence: 99%
“…Although 5-ALA-PDT has been intensively studied for several decades, the mechanism underlying its cytotoxicity is not well known. It has been demonstrated that 5-ALA-PDT leads to apoptosis when PpIX accumulates in the mitochondria and to necrosis when it diffuses into the cytoplasm (7). A previous study reported that 5-ALA-PDT induced autophagic cell death through the activation of adenosine monophosphate-activated protein kinase (AMPK) (8).…”
Section: Introductionmentioning
confidence: 99%